Muito além de audiências, sentenças e recursos: liderança feminina sustentável na advocacia - Silva, Silvia Letícia Ferreira da (2024)
This study explores the presence and impact of sustainable leadership attributes in women holding leadership positions in the legal field, a realm still predominantly male-dominated, although there is a rising trend of women ascending to these roles despite faced resistance. The main goal of the research is to understand how sustainable leadership attributes manifest in the practices of women leaders within the legal context. For this purpose, the attributes identified by Armani (2020) were categorized into three main dimensions: organizational dynamics, management, and sustainable attitudes. The investigation involved women lawyers in management roles at legal departments of companies from Ceará listed on B3, as this setting is often more aligned with ESG (Environmental, Social, and Corporate Governance) practices due to market demands. A qualitative, descriptive, and exploratory methodology was employed, using field research with semi-structured interviews with 17 women leaders. Data were analyzed using Bardin's (2011) content analysis technique. The results show that the leaders exhibit a strong alignment with sustainability principles, demonstrating skills in adapting to organizational culture and fostering an inclusive work environment. Notably, the challenges include resistance to change and some passive stances on the topic, reflecting the need for more robust strategies to overcome such obstacles. This study contributes valuable perspectives to strengthen sustainable female leadership in law and promote more inclusive and responsible professional development.